A Lingering Diminuendo? The Conference on Devolution, 1919–201. (October 2016) - Evans, Adam
Abstract : This article looks at one of the more obscure moments in British constitutional history, the rise of federal devolution in the United Kingdom in the early 20th century and, in particular, the context to the Conference on Devolution that sat between October 1919 and April 1920. The conference, as this article will briefly discuss, has been relegated to footnote status in the historiography on federal devolution and British politics. However, while the conference has not been the subject of detailed academic attention, the claim that devolution and constitutional reform in this period was a by‐product of the crisis in Ireland pre‐partition has gathered considerable traction among political historians. This article will redress both the paltry analysis of the Conference on Devolution within the academic literature and the Irish‐centric historiography on federal devolution in the early 20th century. On the latter front, this article will demonstrate that the conference was the product of forces that extended beyond the Irish crisis, in particular parliamentary congestion. As for the conference itself, this article will use a wide range of archival sources to examine critically the conference's deliberations and in doing so will challenge prevailing assumptions regarding the supposedly one firm source of agreement during the conference: the powers that the devolved bodies should enjoy.